Comparing the ability of OPTION12 and OPTION5 to assess shared decision-making in genetic counselling. Issue 10 (October 2016) - Vortel, Martina A.; Adam, Shelin; Port-Thompson, Ashley V.; Friedman, Jan M.; Grande, Stuart W.; Birch, Patricia H.
Highlights: OPTION 5 demonstrates improved reliability and validity relative to OPTION 12 . OPTION 5 targets constructs specific to SDM allowing for more efficient measurement. Genetic counsellors exhibit shared decision making (SDM) behaviours. Abstract: Objectives: OPTION 12 is the most widely used tool to measure shared decision-making (SDM) in health care. A newer scale, OPTION 5, has been proposed as a more parsimonious measure that better addresses core concepts of SDM. This study compares OPTION 5 to OPTION 12 in prenatal genetic counselling. Methods: Two raters independently used OPTION 12 and OPTION 5 to score 27 clinical encounters between genetic counsellors (GC) and women with pregnancies at increased risk for genetic conditions. Global and item scores on the two instruments were compared to test concurrent validity and to identify usability in this context. Inter-rater reliability was also assessed for both instruments. Results: Mean scores for OPTION 12 were 43.8 (SD = 9.7), and for OPTION 5 were = 60.6 (SD = 12.5). The correlation between OPTION 12 and OPTION 5 scores was r = 0.70. Inter-rater reliability was 0.70 and 0.85 for OPTION 12 and OPTION 5 respectively, however mean inter-rater reliability for individual items was 0.31 and 0.63 for OPTION 12 and OPTION 5 respectively. Conclusions: GCs exhibit SDM as measured by both OPTION instruments. OPTION 5 exhibits improved psychometric performance relative to OPTION 12, and more specifically targets the core constructs of SDM. However, refinement of OPTION instruments or manuals is needed to improve reliability and validity in GC assessment.